2011
DOI: 10.5665/sleep.1380
|View full text |Cite
|
Sign up to set email alerts
|

Treating Obstructive Sleep Apnea with Hypoglossal Nerve Stimulation

Abstract: NCT01186926. URL: http://clinicaltrials.gov/ct2/show/NCT01186926.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
212
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(234 citation statements)
references
References 30 publications
5
212
0
17
Order By: Relevance
“…Thirty patients with obstructive sleep apnea who were implanted with a novel HGNS system (Apnex Medical, Inc., St. Paul, MN) were recruited (23). Written informed consent was obtained.…”
Section: Methods Patient Populationmentioning
confidence: 99%
“…Thirty patients with obstructive sleep apnea who were implanted with a novel HGNS system (Apnex Medical, Inc., St. Paul, MN) were recruited (23). Written informed consent was obtained.…”
Section: Methods Patient Populationmentioning
confidence: 99%
“…After 3 month-long therapy, the Authors reported a decrease in mean AHI by 56% (from 43 to 19), with decreases in total and respiratory-related arousals (47% and 66%, respectively). Sleepiness, sleep quality and quality of life questionnaire scores also improved [62]. However, 71% of patients reported at least one adverse event including tongue abrasion.…”
Section: Osahs Treatmentmentioning
confidence: 94%
“…reported that apnea events and associated daytime symptoms reappeared after 1-week treatment withdrawal [133]. Similarly, Eastwood et al [62] recently carried out a multicenter study involving 21 moderate-to-severe OSAHS patients to test the efficiency of the HGNS® neurostimulator system (Roseville, MN, USA). After 3 month-long therapy, the Authors reported a decrease in mean AHI by 56% (from 43 to 19), with decreases in total and respiratory-related arousals (47% and 66%, respectively).…”
Section: Osahs Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed improvement of sleep parameters [98,104]; others failed to find any effects [105,106]. In a recent study, the authors have shown significant improvement of AHI from 43 to 19/ h with hypoglossal nerve stimulation, however it failed to resolve sleep apnea [107].…”
Section: Hypoglossus Nerve Stimulation and Muscle Trainingmentioning
confidence: 94%